Genetic background of idiopathic neurodevelopmental delay patients with significant brain deviation volume. Issue 7 (5th April 2023) - Chen, Xiang; Chen, Yuxi; Yan, Kai; Chen, Huiyao; Qin, Qian; Yang, Lin; Liu, Bo; Cheng, Guoqiang; Cao, Yun; Wu, Bingbing; Dong, Xinran; Qiao, Zhongwei; et al.
Abstract: Background: Significant brain volume deviation is an essential phenotype in children with neurodevelopmental delay (NDD), but its genetic basis has not been fully characterized. This study attempted to analyze the genetic factors associated with significant whole-brain deviation volume (WBDV). Methods: We established a reference curve based on 4222 subjects ranging in age from the first postnatal day to 18 years. We recruited only NDD patients without acquired etiologies or positive genetic results. Cranial magnetic resonance imaging (MRI) and clinical exome sequencing (2742 genes) data were acquired. A genetic burden test was performed, and the results were compared between patients with and without significant WBDV. Literature review analyses and BrainSpan analysis based on the human brain developmental transcriptome were performed to detect the potential role of genetic risk factors in human brain development. Results: We recruited a total of 253 NDD patients. Among them, 26 had significantly decreased WBDV (<−2 standard deviations [SDs]), and 14 had significantly increased WBDV (>+2 SDs). NDD patients with significant WBDV had higher rates of motor development delay (49.8% [106/213] vs . 75.0% [30/40], P = 0.003) than patients without significant WBDV. Genetic burden analyses found 30 genes with an increased allele frequency of rare variants in patients with significant WBDV. Analyses of the literature further demonstrated that these genes were not randomly identified: burden genes were more related to the brain development than background genes ( P = 1.656e –9 ). In seven human brain regions related to motor development, we observed burden genes had higher expression before 37-week gestational age than postnatal stages. Functional analyses found that burden genes were enriched in embryonic brain development, with positive regulation of synaptic growth at the neuromuscular junction, positive regulation of deoxyribonucleic acid templated transcription, and response to hormone, and these genes were shown to be expressed in neural progenitors. Based on single cell sequencing analyses, we found TUBB2B gene had elevated expression levels in neural progenitor cells, interneuron, and excitatory neuron and SOX15 had high expression in interneuron and excitatory neuron. Conclusion: Idiopathic NDD patients with significant brain volume changes detected by MRI had an increased prevalence of motor development delay, which could be explained by the genetic differences characterized herein.